Assessing Types of Capital Market in the Indonesian Legal System - Katifa, Anjali; Radhia, Muhammad Daffa; Mangundihardjo, Zefanya Queenta (Anthology: Inside Intellectual Property Rights, 2025)
This paper examines the types of capital markets within the Indonesian legal system, starting with their role throughout historical development from the Dutch colonial era to the present day. It highlights the capital market’s pivotal role in building the economic strength of Indonesia, serving as a mechanism for raising long-term funds and facilitating investment opportunities for both individuals and institutions. The study applies a normative legal research method, utilizing secondary data and a literature review to analyze the legal framework and operational structures of Indonesia’s capital markets. Emphasis is given to the distinction between the primary and secondary markets, their respective functions, and the regulatory oversight provided by the Financial Services Authority (OJK) and the Indonesia Stock Exchange (IDX). The paper discusses how legal regulations, particularly Law Number 8 of 1995, support market integrity, investor protection, and transparency. It also explores the types of capital markets viewed from the transaction process, including spot market, futures or forward market, and options market along with the trading mechanism on the stock exchange. Recent trends are also being discussed, such as the rise of retail investors and the impact of digital platforms on market inclusivity. The findings underscore the legal distinctions of each market type and the need for regulatory development to enhance market depth.